Proszę o pomoc!
[tex]x^{3}(x^{4}+2x^{2}-x-1)=[/tex]
[tex](x-1)(x^{2}+x+1)=[/tex]
[tex](x^{2}-1)(x^{5}-x+1)=[/tex]
[tex](5-3x+x^{2})( x^{2} -1) =[/tex]


Odpowiedź :

Odpowiedź:

[tex]x^{3} (x^{4} +2x^{2} -x-1)=x^{7} +2x^{5} -x^{4} -x^{3}[/tex]

[tex](x-1)(x^{2} +x+1)=x^{3} +x^{2} +x-x^{2} -x-1=x^{3} -1[/tex]

[tex](x^{2} -1)(x^{5} -x+1)=x^{7} -x^{3} +x^{2} -x^{5} +x-1=\\ =x^{7} -x^{5} -x^{3} +x^{2} +x-1[/tex]

[tex](5-3x+x^{2} )(x^{2} -1)=5x^{2} -5-3x^{3} +3x+x^{4} -x^{2} =\\ =x^{4} -3x^{3} +4x^{2} +3x-5[/tex]